Faktor-Faktor Yang Mempengaruhi Status Gizi Anak Autis Di Sekolah Kebutuhan Khusus Kota Kediri - Suwoyo Suwoyo (coba, 2017)
The prevalence of autism in Indonesia continues to increase. Children with autism have limited choices of food that may be consumed. This limitation can affect the low or excess intake of nutrients needed by children with autism. Various factors can affect the nutritional status of children with autism. One of them is the pattern of consumption of foods that do not diet GFCF. This study aims to determine the factors that affect nutritional status in children with autism in the School of Special Needs, Kediri. The design used was cross sectional analytic. The population in this study were all children with autism in the School of Special Needs, Kediri, as many as 31 children. The sampling technique used was simple random sampling, with a sample size of 29 children with autism. The result of ordinal regression test to analyze the influence of knowledge on nutritional status was obtained p = 0,038 <α (0,05), socio-economic influence with nutritional status got p = 0,004 <α (0,05), influence of education level with nutrient status got p = 0,412> α (0,05), and the effect of activity pattern with nutritional status obtained p = 0,059n> α (0,05). The conclusion of this research is that based on the results of spearmen test, s then the variables of education, socioeconomic and educational level have correlation with nutritional status of autistic children, while the activity pattern variable is not related to nutritional status of children with autism. Based on testing of ordinal regression analysis it is found that knowledge and socioeconomic of parents influence nutritional status, sedagkan level of education and activity pattern does not affect nutritional status. Therefore, parents at home and school teachers have a very strategic role in providing nutritional intake according to the needs of children with autism, and set the pattern of activities both controlled and uncontrolled. Keywords: factors that affect Nutrition Status, Autis Children